MENGEMBANGKAN KECERDASAN VERBAL LINGUISTIK MELALUI PERMAINAN PALINDROM ANAK USIA 5-6 TAHUN - Artika Sari , Muhamad Ikhsan Fitrah; Indah Sri Mulyani, Nyimas Muazzomi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to develop verbal-linguistic intelligence in children aged 5-6 years through palindrome games. The methods used in this research are literature studies and field experiments, where children are invited to participate in activities that involve searching for and creating palindromes. Data was studi literatur regarding changes in children's language abilities after participating in the game. The results showed that palindrome games significantly improved children's vocabulary, speaking and listening skills. In addition, children also show increased motivation to learn languages, with higher enthusiasm compared to conventional learning methods. These findings indicate that a fun and interactive approach to language learning is very effective in developing the verbal-linguistic abilities of young children. palindrome games can be recommended as an innovative and fun learning method to improve children's language skills.